Acetylcholinesterase (AChE) Expression Demonstrate Differentiation of Nuclei in Rat Brain - Anju, Chouhan; Maheep, Bhatnagar (Asian Journal of Biological and Life Sciences)
Acetylcholinesterase (AChE) plays an important role in synaptic transmission by catalysing hydrolysis of the neurotransmitter Acetylcholine (Ach). Earlier studies have demonstrated non-enzymatic role of AChE in the neuron development and differentiation, growth, formation of neuromuscular junctions, synaptogenesis and survival. A direct correlation between endogenous AChE and neurite outgrowth in primary DRG (Dorsal Root Ganglion) neurons has been also reported. In this study, we demonstrated a direct correlation between expression of endogenous AChE and differentiation of neurons in different nuclei of 3, 7, 12, 21 and 30 days old rat pup brains. We have observed differential histochemical expression of AChE in Fronto Parietal Cortex- Motor and sensory area, Amygdala Nuclei, Hypothalamic Nuclei, Thalamic Nuclei, Interior Capsule, Caudate Putamen and Hippocampus area at different developmental stages. We suggest that AChE expression in neuron cell bodies might be important indicator of differentiation of the nuclei. We thus propose that independent of its catalytic activity, AChE might be playing important role in early development and differentiation of the nuclei in the brain.
Keywords: AChE (Acetylcholinesterase); Amygdaloid Nuclei; Caudate Putamen.; Fronto-parietal cortex; Hypothalamic Nuclei; Thalamic Nuclei